Electrochemical mineralization of norfloxacin using distinct boron-doped diamond anodes in a filter-press reactor, with investigations of toxicity and oxidation by-products - Coledam, Douglas A. C.; Aquino, Jose M.; Silva, Bianca F. [UNESP]; Silva, Adilson Jose; Rocha-Filho, Romeu C. (Elsevier B.V., 2016)
The contamination of water bodies by antibiotics is a cause of concern due to chronic toxic effects and the possible development of resistance to them by microorganisms, which can lead to serious health problems to humans. Thus, in this work, for the first time the degradation of norfloxacin (100 mg L-1 NOR in 0.1 mol L-1 Na2SO4) is carried out electrochemically, using a filter-press flow reactor with boron-doped diamond (BDD) anodes of distinct characteristics. The investigated variables (and their ranges) were solution pH (3, 7, 10, and without specific control), current density (10, 20, and 30 mA cm(-2)), temperature (10, 25, and 40 degrees C), and boron content-sp(2)/sp(3) carbon ratio of the BDD anode (100 ppm - 215, 500 ppm - 325, and 2500 ppm - 284). The NOR electrodegradation performance of the distinct anodes was assessed by monitoring the degradation by-products (aromatic compounds and carboxylic acids), NOR concentration and total organic carbon concentration of the electrolyzed solutions, as well as their toxicity to Escherichia coli (i.e. growth inhibition). For the complete removal of NOR, the best condition (not pH dependent) was attained at 10 mA cm(-2) and 40 degrees C, when the system is under mass transfer limitations. Concerning NOR oxidation and mineralization rates, mineralization current efficiency, energy consumption, and degradation products, similar results (including the complete detoxification of the electrolyzed solution) were attained for all tested BDD anodes under mass or charge transfer controlled processes. Clearly, the oxidation power of the tested BDD anodes is not affected by the values of their boron content-sp(2)/sp(3) carbon ratio. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Conductive diamond anode; fluoroquinolones; electrooxidation; toxicity assay to Escherichia coli